BananaSWaT / Dr. Nor Azliza Akbar - Akbar, Nor Azliza (Unit Penerbitan FKAPP, 2019)
Dye industry is one of the industries that produce high income to economic growth in several countries around the world. However, the wastewater generated contains high organic and inorganic contaminants which exceed the standard effluent of industrial wastewater by Department of Environment. Banana stem is an agricultural plant waste which is among the popular fruit grown in Asia. A few tons per hectare of the banana stem has been estimated annually and lead to disposal issues. Hence, the researchers have invented new adsorbent media known as 'BananaSWaT' function as an adsorbent to overcome the problem.